Effectiveness of Doctoral Defense Preparation Methods - Eva O. L. Lantsoght (MDPI AG, 2022)
The doctoral defense is an important step towards obtaining the doctoral degree, and preparation is necessary. In this work, I explore the relation between the way in which a doctoral candidate prepares for the defense and two important aspects of the defense: the outcome of the defense, and the student perception during and after the defense. I carried out an international survey with an 11-point Likert scale, multiple choice, and open-ended questions on the doctoral defense and analyzed the data of the 204 completed surveys using quantitative and qualitative methods. The methods I used included the statistical tests of the correlation between, on the one hand, the preparation and, on the other hand, the defense outcome and student perception. I used an inductive thematic analysis of the open-ended survey questions to gain a deeper insight into the way candidates prepared for their defense. I found that candidates most often prepare by making their presentation, reading their thesis, and practicing for the defense. The most effective measure is the mock defense, followed by a preparatory course. The conclusion of this work is that doctoral candidates need to understand the format of their defense in order to be able to prepare properly, and that universities should explore either individual pathways to the defense or pilots using a mock defense and/or preparatory course to prepare their doctoral candidates for the defense.